Efikasi Insektisida Berbahan Aktif (klorpirifos 540 g/l dan sipermetrin 60 g/l) terhadap Perkembangan Populasi dan Serangan Hama Penggulung Daun Lamprosema indicata Fabricius (Lepidoptera: Pyralidae) pada Tanaman Kedelai - I WAYAN DIRGAYANA; I KETUT SUMIARTHA; I MADE MEGA ADNYANA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
Efficacy of Insecticide (chlorpyrifos 540 g/l and sipermetrin 60 g/l) Against Population Development and Percentage of Damage of Leaf Roller Insect, Lamprosema indicata Fabricius (Lepidoptera: Pyralidae) on Soybean Plant The research was conducted in order to know the population growth and percentage of damage of soybean leaf roller Lamprosema indicata Fabricius (Lepidoptera: Pyralidae) treated with an insecticide with chlorpyrifos 540 g/l + sipermethrin 60 g/l active ingredient. The research was done in Temesi Village, Gianyar District, Gianyar Regency starting from December 2016 until February 2017. This research used a Randomized Block Design with five (5) levels treatments and five (5) replications. The sampling technique was performed with diagonal pattern and each treatment was taken ten (10) sample of plants. The results showed that population development and percentage of damage of L. indicata influenced by insecticide with active ingredient chlorpyrifos 540 g/l + sipermetrin 60 g/l. The higher dosage was treated will be decreasing the population development and percentage of damage of L. indicata. The higher population and percentage of damage of L. indicata will be decreasing the production of soybean plant.